Nutrient Content, Protein Fractionation, and Utilization of Some Beans as Potential Alternatives to Soybean for Ruminant Feeding - A. Jayanegara; S. P. Dewi; M. Ridla (Media Peternakan, 2016)
This experiment aimed to determine nutrient content, protein fraction, and in vitro rumen fermentation of some alternative beans in comparison to soybean. Samples used were napier grass, soybean, redbean, groundnut, pigeonpea, cowpea, bambarabean, and mungbean. Samples were determined for their proximate composition, Van Soest’s fiber fraction, and Cornell protein fraction. The samples were subsequently evaluated for their fermentation characteristics and digestibility by using a two-stage in vitro rumen fermentation technique, maintained at 39 oC for 2 × 48 h. The in vitro incubation was performed in three consecutive runs by following a randomized complete block design in which each sample per run was represented by four fermentation tubes. Results revealed that all experimental beans contained high crude protein (CP), i.e. above 200 g/kg dry matter (DM), but only soybean and groundnut had CP contents higher than 300 g/kg DM. Redbean had the lowest crude fiber and acid detergent fiber contents among the beans. Soybean contained high proportion of rapidly degraded CP fraction, but low in slowly degraded and unavailable CP fractions. High proportion of slowly degraded CP fraction was found in redbean and bambarabean. Redbean, pigeonpea, cowpea, and mungbean were better than soybean, groundnut, and bambarabean with regard to DM degradability and DM digestibility values (P<0.05). Concentration of total VFA was the highest in the incubation of redbean. It was concluded that groundnut, redbean, pigeonpea, cowpea, and mungbean have the potency to be used to substitute soybean for ruminant feeding.